A Survey on Data Mining Algorithms - Uma; Jayasimman, L; Upendran, V (International Journal of Computer Sciences and Engineering, 2025)
This research paper presents a review of data mining algorithms which is useful to predict the accuracy in the educational domain. It discusses and compares various data mining algorithms in the educational domain. Nowadays it is becoming increasingly important to develop powerful tools for analysis of the enormous data that is stored in databases and data warehouses, and mining such data and arriving at values focused on interesting knowledge from it. Modern organizations focus and put on much thrust in developing data mining procedures and derive benefit from it. Data mining is a process of inferring knowledge from such huge data. There are three major components in Data Mining Viz Clustering, Classification and Association Rules. By discussing the various algorithms this research paper has the scope to extend it further, in order to develop it further in the direction of new and innovative algorithms. The main aim of the paper is to study the effectiveness of various algorithms in the educational environment.